Practically best friends?! Agility and ISO 9001 - Patricia A. Adam (Hochschule Hannover, Fakultät IV - Wirtschaft und Informatik, Abteilung Betriebswirtschaft, 2021)
Agility is considered the silver bullet for survival in the VUCA world. However, many organisations are afraid of endangering their ISO 9001 certificate when introducing agile processes. A joint research project of the University of Applied Sciences and Arts Hannover and the DGQ has set itself the goal of providing more security in this area. The findings were based on interviews with managers and team members from various organisations of different sizes and industries working in an agile manner as well as on common audit practices and a literature analysis. The outcome presents a clear distinction of agility from flexibility as well as useful guidelines for the integration of agile processes in QM systems - for QM practitioners and auditors alike.
urn:nbn:de:bsz:960-opus4-20927
Keywords: 650; Quality Management; QM; Agile Practices; Processes; Agile Manifesto